Little Critter's bedtime storybook - Mayer, Mercer (New York : Golden Book ; Racine, Wis. : Western Pub. Co., 1987)
Finding Little Sister acting selfish, fussy, and grumpy and refusing to go to sleep, Little Critter tells her four bedtime stories in which the characters reflect her bad behavior.
Keywords: Bedtime; Brothers and sisters; Behavior